#TITLE_ALTERNATIVE# - Marada (NIM 132 02 166), Viar
Abstract: Data transmission through a channel will be disturbed by a certain kind of noise. If the distance between sender and receiver is greater then so is the disturbing noise. This wil affect and might change the data that was sent by the sender and render the data unuseable in the receiver.As a result, without a good solution to get rid of the noise, it is almost impossible to send data through a noisy channel or in a long distance. There are some solution for this problem such as by changing the channel transmission media to a more noise-resistance media, building a relay station between the sender and the receiver or add more bandwidth to the data signal. Another solution is by trying to repair the already damaged data. This solution is by using an error correction system which is able to identify the damaged data at a certain limit and return it to original data. The advante of the method is with the present infrastructure and transmitting system, the should-be unused data can be repair and the original data retrieved without add an expensive new infrastructure. This paper will discuss the design of an error correction system with 2D+ and 3D dimension hypercube system. The size of a string of data that will be used in this error correction system are 8x8, 9x9, 10x10 and 11x11 for 2D+ dimension ang 4x4x4, 5x5x5 and 6x6x6 for the 3D dimension error correction system. This system is using parity bit and soft-bit to recognize the damaged data. Then, a performance analysis will be executed for the data that was damaged by noise and the size of gate equivalent will be calculated for each designed system. From this performance analysis, a conclusion wil be drawn to decide which is the best system and size. The designed error correction system can be used in any design of communication chip. However in this paper the main objective is to install the design in power line transmission.